2010
DOI: 10.1007/s00299-010-0962-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genomic DNA of DcACS1, a 1-aminocyclopropane-1-carboxylate synthase gene, expressed in senescing petals of carnation (Dianthus caryophyllus) and its orthologous genes in D. superbus var. longicalycinus

Abstract: Carnation (Dianthus caryophyllus) flowers exhibit climacteric ethylene production followed by petal wilting, a senescence symptom. DcACS1, which encodes 1-aminocyclopropane-1-carboxylate synthase (ACS), is a gene involved in this phenomenon. We determined the genomic DNA structure of DcACS1 by genomic PCR. In the genome of 'Light Pink Barbara', we found two distinct nucleotide sequences: one corresponding to the gene previously shown as DcACS1, designated here as DcACS1a, and the other novel one designated as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 26 publications
3
31
1
Order By: Relevance
“…Carnation (Dianthus caryophyllus L.) 'Light Pink Barbara (LPB)' and D. superbus L. var. longicalycinus 'Metia Pink' (Sakata Seeds Corp., Yokohama, Japan) were the same as used previously (Harada et al, 2011). The other two accessions of D. superbus var.…”
Section: Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Carnation (Dianthus caryophyllus L.) 'Light Pink Barbara (LPB)' and D. superbus L. var. longicalycinus 'Metia Pink' (Sakata Seeds Corp., Yokohama, Japan) were the same as used previously (Harada et al, 2011). The other two accessions of D. superbus var.…”
Section: Plant Materialsmentioning
confidence: 99%
“…DcACS1 was shown to be mainly responsible 444 for autocatalytic ethylene production in the petals (Jones, 2003;Jones and Woodson, 1999;Satoh, 2011;Shibuya and Ichimura, 2010;ten Have and Woltering, 1997); however, the genomic DNA structure of carnation ACS genes had not been reported until fairly recently when Harada et al (2011) investigated the structure of DcACS1 gene. Harada et al (2011) examined the genomic DNA structure of DcACS1 isolated from 'Light Pink Barbara' carnation, and showed that DcACS1 has two variants, distinguishing DcACS1a from DcACS1b. DcACS1a and DcACS1b genes consisted of five exons and four introns.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…exogenously applied ethylene has been found to induce autocatalytic ethylene production in petals of D. superbus var. longicalycinus with simultaneous accumulation of transcripts of DsuACS1 (Harada et al 2011a). ACC oxidase gene has been isolated from carnation (wang and woodson 1991).…”
Section: Genes Involved In Ethylene Synthesis (Acc Synthase and Acc Omentioning
confidence: 99%